Beginning of a New Era in Hungarian Crop Production - Bocz, Ernő (Acta Agraria Debreceniensis, 2002)
The examination of Triticum monococcum, which was observed on an ancient region, and its ancient quality made me develop a new quality analysis system.The Triticum Monococcum frames the new standard of this ancient quality.The quality of diploidea – tetraploidea – hexaploidea series, which was arisen by the wheat poliploidization, gradually decreased. The quality of diploidea species diffuse around the standard.The micronutrient content of tetraploid species gradually decrease, the hexaploid species and the Triticum Aestuvum micronutrient content 20-70% less than the ancient quality’s.